Analysis of the Possibilities of Using HBIM Technology in the Protection of Cultural Heritage, Based on a Review of the Latest Research Carried out in Poland - Dorota Janisio-Pawłowska (ISPRS International Journal of Geo-Information, 2021)
The implementation of HBIM technology in the research carried out with historical objects remains at a very early stage and constitutes only a fracture of current studies, including in Poland. This process becomes indispensable for the analysis of the existing condition, management and protection of cultural heritage. Therefore, it proves necessary to elaborate directions and guidelines for the implementation of HBIM technology. The present article deals with research and analysis of Polish conservation studies. We discuss the methods for recording information, the scope and detail of the elaborated 3D model, including library objects. The possibility of further editing of objects, the digital tools applied and the data recording formats were all analyzed. The tables present the discrepancies in the creation of 3D objects. We described and compared the studied objects. The collected analyzes were used to summarize important parameters and collected data. This in turn allowed us to elaborate universal guidelines that could be used in the implementation of HBIM technology in other countries as well. Digital tools and data recording formats used to develop the discussed models of objects pave the way to the possibility of further editing and implementation of HBIM technology.